Dracorhodin: A potential marker compound for detecting the presence of dragon’s blood resin from Daemonorops originated from Indonesia - TOTOK KARTONO WALUYO; SANTIYO WIBOWO (Biodiversitas Journal of Biological Diversity, 2018)
Waluyo TK, Wibowo S. 2018. Dracorhodin: A potential marker compound for detecting the presence of dragon’s blood resin from Daemonorops originated from Indonesia. Biodiversitas 19: 1665-1671. Dragon's blood typifies as red-colored resin, which is presented by several plant genus, i.e., Dracaena, Daemonorops, Croton, and Pterocarpus. In Indonesia, dragon's blood is originated from Daemonorops which grows scattered in Sumatera and Kalimantan islands. Relevantly, this study was conducted to identify the specific compounds of dragon's blood originated from Indonesia's Daemonorops. Dragon's blood test samples were originated from 16 different towns in Indonesia, which are known as the center of dragon's blood-production. The samples were in powder and solid formation. The compounds of samples were analyzed using GC-MS instrument. Results revealed that dragon's blood in powder and solid formation were inherently similar. Dragon's blood powder was obtained from wet extraction, while dragon's blood solid from dry extraction. Results of chemical analysis on 16 dragon's blood samples disclosed that three compounds were frequently detected associated with dragon's blood presence. Dracorhodin compound was detected in 16 dragon's blood samples i.e 3,4-dihydro-5-methoxy-6-methyl-2-phenyl-2H-1-benzopyran-7-ol in 13 samples; and trendione in 9 samples. Accordingly, dracorhodin could serve as the most compound containing in dragon's blood originated from Indonesia's Daemonorops, which could be observed from 16 tested Daemonorops dragon's blood samples from several regions (towns) in Indonesia.